PENGARUH CORPORATE SOCIAL RESPONSIBILITY GOAL, CORPORATE SOCIAL ISSUE, DAN CORPORATE RELATION PROGRAM TERHADAP KESEJAHTERAAN MASYARAKAT PADA PT. PERKEBUNAN NUSANTARA VII (PERSERO) UNIT USAHA KOTA PAGARALAM - Masayu Mikial; Kusminaini Armin; Anggara Ardyagarini Pamungkas (JURNAL KOMPETITIF, 2016)
The purpose of this study is to determine how much influence the Goal of Corporate Social Responsibility, Corporate Social Issue, and Corporate Relations Program as independent variables together against Public Welfare as the dependent variable at PT. Perkebunan Nusantara VII Business Unit Pagaralam City.Mechanical sampling using simple random sampling with a sample of 133 people. The technique used is quantitative and qualitative techniques that use the questionnaire as a means of collecting data and using multiple linear regression analysis technique to measure the influence of independent variables on the dependent variable. The data in this study assisted by the Statistical program For Product and Service Solutions (SPSS) version 22. The design used in this study using associative method is research that aims to determine the influence or relationship between two or more variablesThe results of this study stated that Corporate Social Responsibility Goal, Corporate Social Issue and Corporate Relations Program jointly effect on the welfare of society at PT. Perkebunan Nusantara VII Business Unit Pagaralam City. Based on the results of multiple linear regression equation: Y = 25 833 + + 0,239X3 0,063X2 0,395X1 + + e and has a coefficient (R) of = 0.631 and the coefficient of determination (R2) = 0.398 it is clear that the welfare of society (the dependent variable) explained by Goal Corporate Social Responsibility, Corporate Social Issue and Corporate Relations Program (independent variable) amounted to 39.8%. And the balance of 60.2% is explained by other factors not examined in this study. Keywords: Goal of Corporate Social Responsibility, Corporate Social Issue, Corporate Relations Program, Community Welfare